CoronaVR: A Computational Resource and Analysis of Epitopes and Therapeutics for Severe Acute Respiratory Syndrome Coronavirus-2 - Gupta, Amit Kumar; Khan, Md. Shoaib; Choudhury, Shubham; Mukhopadhyay, Adhip; Sakshi,; Rastogi, Amber; Thakur, Anamika; Kumari, Pallawi; Kaur, Manmeet; Shalu,; Saini, Chanchal; Sapehia, Vandna; et al. (Frontiers in Microbiology, 2020)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a recently discovered emerging pathogenic RNA virus strain responsible for infectious COVID-19 disease. WHO declared COVID-19 as Public Health Emergency of International Concern (PHEIC) and later characterized it as a global pandemic with more than 14 million infected people and over 88000 deaths. Hence, there is an urgent need for a vaccine and therapeutics to put the curb on SARS-CoV-2 and its associated disease, i.e., COVID-19. The global efforts are underway to circumvent its further spread and treat the affected one through vaccine formulations and therapeutic interventions respectively. However, there is no FDA-approved drug with proven clinical efficacy or a vaccine available till date with several candidates being under clinical testing. Therefore, to accelerate the global efforts in a fight against the SARS-CoV-2, we have come up with bioinformatics-based approaches to assist the researchers at initial phase of vaccine and therapeutics development. In this study, we have performed comprehensive meta-analyses and developed an integrative resource “CoronaVR” (http://bioinfo.imtech.res.in/manojk/coronavr/). Predominantly, we recommend the potential epitope-based vaccine candidates, siRNA-based therapeutic regimens and diagnostic primers. The resource is categorized into various sections like “Genomes”, “Epitopes”, “Therapeutics”, and Primers”. The genome section harbors different components viz genomes, browser, phylogenetic analysis, codon usage, glycosylation sites and structural analysis. Under the umbrella of epitopes, sub-divisions namely cross-protective epitopes, IEDB, B-cell (linear/discontinuous), T-cell (CD4+/CD8+), CTL, and MHC binders are presented. Therapeutics section has different sub-sections like siRNA, miRNAs, and sgRNAs. Further, experimentally confirmed and designed diagnostic primers earmarked in the primers section. Our study provided a set of shortlisted B-cell and T-cell (CD4+ and CD8+) epitopes that can be experimentally tested for their incorporation in vaccine formulations. The shortlisted T-cell epitopes were expected to provide widespread coverage of human community globally, including the SARS-CoV-2 outbreak center, the mainland China. The selected primers list can be used in testing kits to identify SARS-CoV-2 while the recommended siRNAs, sgRNAs and miRNAs can be used in therapeutics regimens. We foresee this resource will help in advancing the research against the coronaviruses.